Diseño y Construcción de una Interfaz y Plataforma de Comunicación para Monitoreo y Control de un Medidor SMART de Energía Eléctrica en la Ciudad de Loja. - Toledo Iñiguez, Pablo David (2019)
The present work of qualification is the continuation of the thesis "DESIGN AND IMPLEMENTATION OF AN INTELLIGENT READING PROTOTYPE OF ELECTRICAL PARAMETERS, FOR ITS INTEGRATION IN BIPASSICAL ENERGY METERS OF THE CITY OF LOJA" belonging to Diego Fernando Azanza Ordóñez, the union of these Two works make up a macro project, which performs the reading, storage, processing of information and also the cutting and reconnection of the electrical service. For this reason, through this research work it is showed the design and construction of an interface and communication platform for monitoring and control of an electrical energy smart meter in Loja city. The communication module consists mainly of a Raspberry pi 3 and some external components, which emulates the functions of a smart electric power meter, the most important functions are: to send stored information on the Raspberry to a database and to allow the remote management of an actuator that simulates the cutting and reconnection of the electric service. The web platform has a user interface that allows to read the data from the Raspberry and store it in a database, to later manage this information. In addition, the platform has the functions of sending cutting or reconnection orders of the electric service to the Raspberry, according to the case. Additionally, the platform generates a report of the rates to be canceled by the user, based on the values of the items currently invoiced by EERSSA. The web platform has three types of users, Administrator, Billing and Customer, each one with specific privileges, for instance, customers can continuously monitor the status of their electric service and the rates to be paid. For the development of the web platform two web development frameworks are used, Angular for the Front-end and Django for the Back-end, in addition the MySQL database manager is used to store the information coming from the Raspberry, and the server of RabbitMQ message queue for sending this information and the orders for cutting and reconnecting the service.